2011
DOI: 10.1002/pbc.23100
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric palliative care provision around the world: A systematic review

Abstract: Pediatric palliative care is recommended by many organizations. Yet, there is no information available on the progress that has been made in providing this care or the gaps that still exist in provision around the world. We conducted a systematic review to address this gap in knowledge. The systematic review identified 117 peer-reviewed and non-peer reviewed resources. Based on this information, each country was assigned a level of provision; 65.6% of countries had no known activities, 18.8% had capacity build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
131
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 47 publications
2
131
0
7
Order By: Relevance
“…5,[18][19][20][21][22][23][24] Our data also support the notion that appropriate PPHC provided by a specialized team is able to alleviate caregivers' psychological distress and burden. 5,[25][26][27][28] Knapp and colleagues 29 analyzed the status of PPC provision around the world, emphasizing the importance of future advancement in this field. But since the majority of existing studies have taken place after the death of a child, little data are available on the caregivers' needs and experiences with PPHC during the child's illness to date.…”
Section: Discussionmentioning
confidence: 99%
“…5,[18][19][20][21][22][23][24] Our data also support the notion that appropriate PPHC provided by a specialized team is able to alleviate caregivers' psychological distress and burden. 5,[25][26][27][28] Knapp and colleagues 29 analyzed the status of PPC provision around the world, emphasizing the importance of future advancement in this field. But since the majority of existing studies have taken place after the death of a child, little data are available on the caregivers' needs and experiences with PPHC during the child's illness to date.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, a systematic review of children's palliative care worldwide found that 65% of countries had no known children's palliative care. However, 18% had building activities, 9% were able to cite examples of local provision but only 5% had existing children's palliative care (Knapp et al, 2011). Therefore, the provision of high quality palliative care for children and young people remains a global concern (Downing, Marston, & Boucher, 2010).…”
Section: Context Of Paediatric Palliative Carementioning
confidence: 99%
“…Some individual service-providers have undertaken internal evaluations and, although findings may be insightful for the organisations concerned, in general, there is no robust evidence on which to base care in the community (Knapp & Contro, 2009). Never-the-less much of the literature focuses on the care of children and young people with palliative care needs and cancers (Huijer, Sagherian, & Tamin, 2013;Knapp et al, 2011).…”
Section: Context Of Paediatric Palliative Carementioning
confidence: 99%
“…Information and education on palliative medical care, achieving universal coverage of children needing palliative care, taking measures to improve the quality and safety of palliative care based on the needs of local communities [18].…”
Section: Discussionmentioning
confidence: 99%